Eliminating Cervical Cancer in Mali and Senegal, Two Sub-Saharan Countries: Insights and Optimizing Solutions - Azizul Haque; Bourèma Kouriba; N’diaye Aïssatou; Anudeep Pant (Vaccines, 2020)
Background: The number of cases with cervical cancer is rapidly increasing in Sub-Saharan Africa driven by inadequate rates of human papilloma virus (HPV) vaccination and screening programs and accompanied by poor health delivery systems. There are other factors to contend with such as lack of awareness, social myths, reluctance to vaccine acceptance and stigma with sexually transmitted diseases. Here, we formulate strategies to implement intervention programs against HPV infections and other risk factors for cervical cancer in these countries. Methods: We searched PubMed, Web of Science, and African Journals Online for this review. The current status of anti-HPV vaccination and precancerous screening programs in Mali and Senegal has been assessed by onsite visits. Collaborators from Mali and Senegal collected data and information concerning HPV vaccination and screening programs in these countries. Findings: We found that anti-HPV vaccination and cervical cancer screening have been conducted sporadically mainly in urban areas of Mali and Senegal. No known population-based programs are in progress in either of the two countries. We highlighted the advantages and drawbacks of currently available screening tests and proposed that screening by visual inspection with acetic acid (VIA) accompanied by self-sampling is the most cost-effective, culturally acceptable and most feasible strategy to implement in primary care settings. In addition, HPV DNA testing would be affordable, if local laboratory facilities could be established. We found that many of the factors that increase HPV acquisition and promote the oncogenic effect of the virus are largely widespread in both Senegal and Mali. These include infections with HIV and other sexually transmitted infections (STIs), immunosuppression, polygamous marriages, high parity, early sexual activities, early pregnancies, and multiple sexual partners. Interpretation: Neither vaccines nor screening tests are within the reach of the population in Mali and Senegal because of the high cost. The effective intervention measure would be to integrate anti-HPV vaccines into the Extended Program for Immunization (EPI), which has saved 3 million young lives per year in Africa with the support of GAVI, to implement cost control mechanisms for HPV vaccinations via price negotiations with manufacturing companies, as has recently been done by Rwanda. The collective efforts by local governments, researchers, private sector, and donors may lead to the introduction of affordable screening tests. A robust awareness campaign coupled with sustained and regular engagement of local communities about the prevention and risk factors is extremely important. The projected solutions may be well applicable to other Sub-Saharan countries that face similar challenges containing cervical cancer.